Associação da expressão das proteínas KI-67 e MYC na presença do papilomavírus humano (HPV), detectado por hibridização in situ, em neoplasia intraepitelial cervical (NIC). - Lemos, Erika Hardy (2013)
Cervical cancer begins with the progression of premalignant lesions known as cervical intraepithelial neoplasia (CIN). Some evidence has suggested the involvement of the Human Papillomavirus (HPV) in the process. The viral infection induces the expression of markers that have a direct relationship with the neoplastic process and may be used as an additional tool for the diagnosis. In this context, this study aims to associate the presence of HPV with the expression of Ki-67 and MYC protein in women with CIN patients. The study included 173 patients treated in clinics of the MEAC Cervical Pathology. In all, the suspicious lesions were biopsied and sent to the pathology laboratory of the UFC for histopathology. The biopsied tissue was subjected to in situ hybridisation for HPV detection by GenPoint® method and immunohistochemistry for the identification of cellular proteins Ki-67 and MYC through the streptavidin-biotin-peroxidase method. The patients were aged 14-54 years (median 30 years). Histopathological analysis revealed, for the diagnosis of CIN, 41% were CIN I, 24.9% CIN II and CIN III 34.1%. Considering the age group, there was a positive correlation when combined with the degree of NIC (p = 0.001), the highest frequency of CIN III in patients aged 31-40 years. The presence of HPV was detected in 17.3% of cases. The cell proliferation marker Ki-67 was positive in 80.3% of samples. The positivity of this marker was 40.3% in patients with CIN I, 26.6% with CIN II and CIN III with 33.1%. Whereas the presence of HPV, it was observed that 100% of cases were positive for Ki-67 score (p = 0.000). Analysis of the nuclear expression of MYC protein identified positive in 61.8% of cases. Among the patients with a diagnosis of CIN, it can be observed that it was positive for the marker MYC, 42% in patients with CIN I to CIN II 26.2% and 31.8% with CIN III. The presence of HPV was found in 83.3% in the case of a positive MYC, showing a positive correlation (p = 0.007). The analysis of Ki-67 showed that the cell proliferation index can be the difference between degrees of injury. It was also observed that the MYC dysregulation appears to be an early and independent of the presence of HPV event and concomitantly the expression of MYC and Ki-67 may be associated with the severity of the lesions in the presence of the virus. These findings can be used as an important tool in the evaluation of precursor lesions of cervical cancer, favorendo with a good prognótico in the early appearance of the lesions.